Trends in Medically Integrated Dispensing Among Oncology Practices. Issue 10 (13th October 2022) - Kanter, Genevieve P.; Parikh, Ravi B.; Fisch, Michael J.; Debono, David; Bekelman, Justin; Xu, Yao; Schauder, Stephanie; Sylwestrzak, Gosia; Barron, John J.; Cobb, Rebecca; Qato, Dima M.; Jacobson, Mireille
Abstract : PURPOSE: The integration of pharmacies with oncology practices—known as medically integrated dispensing or in-office dispensing—could improve care coordination but may incentivize overprescribing or inappropriate prescribing. Because little is known about this emerging phenomenon, we analyzed historical trends in medically integrated dispensing. METHODS: Annual IQVIA data on oncologists were linked to 2010-2019 National Council for Prescription Drug Programs pharmacy data; data on commercially insured patients diagnosed with any of six common cancer types; and summary data on providers' Medicare billing. We calculated the national prevalence of medically integrated dispensing among community and hospital-based oncologists. We also analyzed the characteristics of the oncologists and patients affected by this care model. RESULTS: Between 2010 and 2019, the percentage of oncologists in practices with medically integrated dispensing increased from 12.8% to 32.1%. The share of community oncologists in dispensing practices increased from 7.6% to 28.3%, whereas the share of hospital-based oncologists in dispensing practices increased from 18.3% to 33.4%. Rates of medically integrated dispensing varied considerably across states. Oncologists who dispensed had higher patient volumes ( P < .001) and a smaller share of Medicare beneficiaries ( P < .001) than physicians who did not dispense. Patients treated by dispensing oncologists had higher risk and comorbidity scores ( P < .001) and lived in areas with a higher % Black population ( P < .001) than patients treated by nondispensing oncologists. CONCLUSION: Medically integrated dispensing has increased significantly among oncology practices over the past 10 years. The reach, clinical impact, and economic implications of medically integrated dispensing should be evaluated on an ongoing basis.